Islamic Views on Radicalism and Terrorism - putrie dewi mayang sari; Rahayu Novaliana Putri; Ramizard Kumbi; Asep Abdul Muhyi (Bulletin of Islamic Research, 2024)
This research aims to get to know Islam, Radicalismand Terrorism. This research is qualitative researchwith descriptive methods and Maudhu'iinterpretation. This type of qualitative approach isbased on secondary data sources which are literature related to the research topic sourced fromarticles, journals, books, etc. Data analysistechniques are carried out through the stages ofinventory, classification and interpretation. The technique for checking the validity of the data iscarried out by means of library research. The research results obtained show that there are several findings obtained by the author, namely, a description of the concept of Islam, the problem ofRadicalism and Terrorism, the history of the birth ofRadicalism and Terrorism, several interpretationswith Maudhu'i interpretations relating to Islam, Radicalism and Terrorism.